1999
DOI: 10.1046/j.1365-8711.1999.02809.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of superbubbles and the detection of Ly  in star-forming galaxies

Abstract: The detection of Lyα emission in star‐forming galaxies in different shapes and intensities (always smaller than predicted for case B recombination) has puzzled the astronomical community for more than a decade. Here we use two‐dimensional calculations to follow the evolution of superbubbles and of the H ii regions generated by the output of UV photons from massive stars. We show the impact caused by massive star formation in the ISM of different galaxies and we look at the conditions required to detect Lyα emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
158
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(171 citation statements)
references
References 36 publications
12
158
1
Order By: Relevance
“…This is also the result obtained from numerical calculations that consider both the mechanical energy of massive stellar clusters as well as their ionizing luminosity. Tenorio-Tagle et al (1999) have shown how once the shell of swept up matter becomes Rayleigh-Taylor unstable and fragments, as it evolves out of a galaxy disk into the halo (the blowout phenomenon), it then allows not only for the venting of the hot (wind and supernovae) matter into the halo, but also for the leakage of a large fraction of the ionizing radiation. The latter soon establishes a giant conical H ii region in the low-density halo.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the result obtained from numerical calculations that consider both the mechanical energy of massive stellar clusters as well as their ionizing luminosity. Tenorio-Tagle et al (1999) have shown how once the shell of swept up matter becomes Rayleigh-Taylor unstable and fragments, as it evolves out of a galaxy disk into the halo (the blowout phenomenon), it then allows not only for the venting of the hot (wind and supernovae) matter into the halo, but also for the leakage of a large fraction of the ionizing radiation. The latter soon establishes a giant conical H ii region in the low-density halo.…”
Section: Discussionmentioning
confidence: 99%
“…Tenorio-Tagle et al (1999) point out that superbubbles may initially expand with speeds that well exceed the local escape velocity of the galaxy but their motion into the gaseous halo causes a continuous deceleration lowering the velocity to values well below the escape speed. In such a case, ejecta condense into a cold phase, forming droplets that fall back and settle down onto the disc of the galaxy hence changing the composition of the ISM (the "Galactic fountain" model).…”
Section: Outflows and Inflowsmentioning
confidence: 97%
“…Kunth et al (1998) found that the strength of Lyα emission is in fact only weakly correlated with metallicity and suggested that the dynamical state of ISM is also a major regulating mechanism. A new model explains Lyα profiles in starburst galaxies by the hydrodynamics of superbubbles powered by massive stars (Tenorio-Tagle et al 1999). Searle and Sargent (1972) had already speculated on the reasons for a sudden increase of the star formation rate in BCGs, followed by long quiescent phases.…”
Section: Gas Content and Dynamics Of Bcgsmentioning
confidence: 99%
“…If the neutral ISM is static with respect to the sources of Ly photons, then the covering factor of the neutral gas becomes important (Kunth et al 1998). Using such observational evidence, Tenorio-Tagle et al (1999) have developed a detailed model for the way in which outflow kinematics determine the emergent Ly profile in starburst galaxies.…”
Section: Ly Dependencesmentioning
confidence: 99%